PROFIL PEMAKAIAN KONTRASEPSI: DISPARITAS ANTARA PERDESAAN DAN PERKOTAAN - Resti Pujihasvuty (Jurnal Kependudukan Indonesia, 2017)
Contraceptive use is one of the essential influential factors to the birth rate of Indonesia. This article aims to identify the profile of contraceptive use in rural and urban areas based on the socio-economic and demographic characteristics as well as the influential factors. This study conducted a further analysis of Performance Monitoring and Accountability 2020 (PMA2020) survey in 2015, by applying univariate, bivariate, and multivariate analysis. The results of the analysis show a similar average number of children for both rural and urban areas; this situation is in accordance with the program of National Population and Family Planning (BKKBN). In addition, the educational and economic status of women in union of childbearing age in rural areas has improved along with the increasing number of women graduated from senior high school as well as the improvement of their wealth. However, many women in rural and urban areas never have been visited by family planning officers as well as do not have health insurance, such as BPJS. The finding of the study also shows that the higher the economic status of women in rural areas, the higher their chances to use contraception. Conversely, the higher the economic status of women in urban areas, the lower their participation in family planning program. Therefore, specific, intensive and equal interventions to IEC and advocacy programs are needed for both rural and urban areas.